Pengaruh Teknik Relaksasi Afirmasi terhadap Stres Mahasiswa yang Menempuh Skripsi di Program Studi Ilmu Keperawatan Universitas Jember - Rommiyatun Zainiyah; Erti Ikhtiarini Dewi; Wantiyah Wantiyah (Pustaka Kesehatan, 2018)
One of stressor in college students is taking a final project as a graduation requirement. The body'sresponse toward stress includes a rise of heart rate, diarrhea and insomnia. One of stressmanagement is affirmation relaxation (AR) technique. This research aimed to analyze the influenceof AR technique towards stress on students who take a final project in Faculty of Nursing, UniversityOf Jember. This research used a quasi experiment with Pretest-Post test approach and controlgroup design. Sampling technique that used is purposive sampling with respondent divided into twogroups, the treatment group and control group with 15 respondents for each group. Data wasanalyzed by using Dependent t test and Independent t test with 95% CI. The result showed thatthere was a significant difference stress before and after given AR technique within average 19,2 to10,87 (p = 0,001). Mean while, there was no significant difference of stress between pretest and posttest in control group within average 18,73 to 18,4 (p = 0,841). Overall, there was a difference ofstress between treatment group and control group (p =0,02, α = 0,05). The AR techniques reducestress because it can influence the sympathetic and parasympathetic nerves to produce endorphinehormone. The conclusion of this research is there was an influence of AR technique towards stresson students who Taking a Final Project in Faculty of Nursing University of Jember.Keywords: affirmation relaxation technique, stress, final project.